2009
DOI: 10.4156/jdcta.vol3.issue2.khan
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Information System for Blood Donation

Abstract: This research work is an attempt to practically implement the Information Technology in real world problems. This system provides multiple facilities, i.e. maintaining record, analysis of various parameters for research issues and providing online information.Hardly there exist such types of online systems in Pakistan that can serve mankind and save precious lives. This system enables users to search, collect and donate blood to the patients who are waiting for the last drop of the blood and are nearby to deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…There is consequently a need to recruit and retain more blood donors, which has traditionally been done using methods such as brochures [26] or videos [27]. In Pakistan, a web-based information system was developed to enable users to search for, collect and donate blood [28], apps related to BD could help attract more volunteers, especially young donors [29]. There is a tremendous lack of studies on BD apps, and no studies on BD apps have been identified with the exception of one thesis [30].…”
Section: Introductionmentioning
confidence: 99%
“…There is consequently a need to recruit and retain more blood donors, which has traditionally been done using methods such as brochures [26] or videos [27]. In Pakistan, a web-based information system was developed to enable users to search for, collect and donate blood [28], apps related to BD could help attract more volunteers, especially young donors [29]. There is a tremendous lack of studies on BD apps, and no studies on BD apps have been identified with the exception of one thesis [30].…”
Section: Introductionmentioning
confidence: 99%
“…The research questions were defined based on good practices in the implementation and use of an online grant platform proposed by Bloch et al (2014) and Heyman (2016). Additionally, the technical practices implemented in the project for nonprofit organizations carried out by Khan & Qureshi (2009) were also considered. Thus, the following research questions were established:…”
Section: Research Questionsmentioning
confidence: 99%
“…This situation is confirmed in the study developed by Umapathy & Huang (2015), which refer that most nonprofit organizations do not have a technology plan and adopt information technologies in a pragmatic way. Although the number of initiatives is small, it is worth mentioning the implementation of a web information system that allows to register and to carry out researches of blood donors (Khan & Qureshi, 2009). The system offers security mechanisms against possible unauthorized access that may alter the data.…”
Section: Introductionmentioning
confidence: 99%
“…It provides multiple facilities, i.e. maintaining record, analysis of various parameters for research issues and providing online information [3].…”
Section: Introductionmentioning
confidence: 99%